2021
DOI: 10.3390/pr9020224
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Peptide-Modified Extracellular Vesicles Enable Effective Intracellular Delivery via the Induction of Macropinocytosis

Abstract: We previously reported that macropinocytosis (accompanied by actin reorganization, ruffling of the plasma membrane, and engulfment of large volumes of extracellular fluid) is an important process for the cellular uptake of extracellular vesicles, exosomes. Accordingly, we developed techniques to induce macropinocytosis by the modification of biofunctional peptides on exosomal membranes, thereby enhancing their cellular uptake. Arginine-rich cell-penetrating peptides have been shown to induce macropinocytosis v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…To integrate the peptides on EV membranes, we adopted a stearyl moiety-based peptide-modification method that was previously developed by us and is characterized by its easy handling. ,, In this study, we isolated EVs using ultracentrifugation methods . The isolated EVs were confirmed by western blotting analysis (Figure S2A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To integrate the peptides on EV membranes, we adopted a stearyl moiety-based peptide-modification method that was previously developed by us and is characterized by its easy handling. ,, In this study, we isolated EVs using ultracentrifugation methods . The isolated EVs were confirmed by western blotting analysis (Figure S2A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, N-terminal stearylated peptides were used to modify the membranes of the EVs (Figure B,C). Recently, we have already highlighted a functional peptide modification system on EV membranes, including: (1) membrane insertion using a hydrophobic moiety with conservation for functionality of EV membrane proteins; however, this noncovalent binding might affect binding efficacy during EV-based delivery, especially in vivo; ,, (2) covalent binding of the peptides with amino acid side chains of EV membrane proteins using, for example, a bivalent linker (succinimide for amino groups of the proteins); however, this covalent binding might affect the functionality of EV membrane proteins; ,, and (3) charge interaction methods, including modification of objective molecules on negatively charged EV membranes using cationic lipids; however, this noncovalent binding might also affect binding efficacy during EV-based delivery, especially in vivo. Simple modification of the stearyl moiety to the sC18 or (sC18) 2 peptides resulted in the decoration of the peptides on the EV membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, functionalization of peptides onto the exosome surfaces may bring about substantial advantages for selective target binding and therapeutic effects for brain tumor treatment [ 126 ]. In this regard, biofunctional peptide-modified exosomes, as novel drug delivery systems, have been previously developed and successfully demonstrated [ 127 ]. Various studies have also practiced the peptide functionalization of exosomes for glioma therapy [ 126 , 128 , 129 ].…”
Section: Peptide Functionalization Of Exosomes For Glioma Therapymentioning
confidence: 99%
“…The result showed that EVs can be employed to target the EGFR expressing cancer tissue with nucleic acid drug for therapeutic purposes [159]. In another research study, Nakase et al developed a novel drug delivery system based on biofunctional peptide-modified exosomes, which includes arginine-rich cell-penetrating peptide-modified exosomes for the active induction of micropinocytosis and the effective intracellular delivery of therapeutic molecules, a pH-sensitive fusogenic peptide for enhanced cytosolic release of exosomal contents, and a receptor target system using an artificial coiled-coil peptide modified on exosomal membranes [160].…”
Section: Conjugation Of Peptides and Extracellular Vesicles (Cpevs) For Cancer Therapymentioning
confidence: 99%